Narrative Form Revised and Expanded Second Edition - Keen, Suzanne; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This revised and expanded handbook concisely introduces narrative form to advanced students of fiction and creative writing, with refreshed references and new discussions of cognitive approaches to narrative, nonfiction, and narrative emotions.
Keywords: Literature, Medieval; Motion pictures—History.; Communication; Language and languages—Style.; Computer science; Literature—Philosophy.; Medieval Literature; Film History; Media Studies; Stylistics; Popular Computer Science; Literary Theory